Characterization and optimization of an electro-thermal microactuator for precise track positioning. Issue 6 (19th September 2017) - Yang, Fan; Xie, Qikai; Zhang, Xiaolong; Chen, Xiaolin
ABSTRACT: This paper presents a MEMS mirror actuated by four suspended electro-thermal bimorphs. The dimension of the mirror platform is 250 µm × 250 µm. The MEMS mirror design is created based on process modeling following strict fabrication constraints. Transient and dynamic characteristics of the micromirror device are analyzed using coupled electro-thermal-mechanical finite element models and schematic behavior models, respectively. The design is optimized using experimental design and response surface methodology to achieve large actuation displacement and small lateral shift. The micromirror device is shown to have a uniform mirror platform deflection, a large resonant frequency adequate to support the high servo bandwidth control, as well as an excellent linear relation between the micromirror deflection and the input electric power. The proposed electro-thermal MEMS mirror is capable of generating a mirror displacement of 8.25 µm under a 3 V pulse voltage input, and can potentially be used as a fine-tracking device for high-density data storage applications. GRAPHICAL ABSTRACT: